2002
DOI: 10.7589/0090-3558-38.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Raccoons (Procyon Lotor) to Infection With Mycobacterium Bovis

Abstract: Tuberculosis due to Mycobacterium bovis infection is endemic in white-tailed deer (Odocoileus virginianus) in the northeastern portion of the lower Michigan peninsula (USA). Various wild carnivores and omnivores, including raccoons (Procyon lotor), are infected with M. bovis within the endemic area. To investigate the pathogenesis of tuberculosis in raccoons and the likelihood of M. bovis transmission from infected raccoons to other susceptible hosts, we experimentally inoculated raccoons with single oral dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Compared with other species like ferrets, in which one single oral dose resulted in lesion development and isolation of M. bovis in all of the animals, raccoons seem relatively resistant to oral M. bovis infection. This fact, together with the low number of orally inoculated raccoons that were able to excrete M. bovis in nasal secretions or saliva in the experiment suggested that in nature where the most probable way of infection is orally, a widespread tuberculosis among raccoons is unlikely (Cross et al 2000;Palmer et al 2002).…”
Section: Bacterial Diseasesmentioning
confidence: 88%
“…Compared with other species like ferrets, in which one single oral dose resulted in lesion development and isolation of M. bovis in all of the animals, raccoons seem relatively resistant to oral M. bovis infection. This fact, together with the low number of orally inoculated raccoons that were able to excrete M. bovis in nasal secretions or saliva in the experiment suggested that in nature where the most probable way of infection is orally, a widespread tuberculosis among raccoons is unlikely (Cross et al 2000;Palmer et al 2002).…”
Section: Bacterial Diseasesmentioning
confidence: 88%
“…At necropsy, the following tissues or fluids were collected and processed for isolation of M. bovis and microscopic analysis as described previously (26): palatine tonsil, lung, liver, and the mandibular, parotid, medial retropharyngeal, tracheobronchial, mediastinal, hepatic, mesenteric, and prefemoral lymph nodes. Tissues were processed for isolation of M. bovis as previously described (27). Isolates of M. bovis were identified by colony morphology, growth, and biochemical characteristics as well as by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…At necropsy, the following tissues or fluids were collected and processed for isolation of M. bovis and microscopic analysis as described [16]; palatine tonsil, lung, liver, mandibular, parotid, medial retropharyngeal, tracheobronchial, mediastinal, hepatic, mesenteric and prefemoral lymph nodes. Tissues were processed for isolation of M. bovis as previously described [17]. Isolates of M. bovis were identified by colony morphology, growth, and biochemical characteristics as well as by PCR.…”
Section: Necropsy and Tissue Samplingmentioning
confidence: 99%